A Comparative History of Commerce and Industry, Volume I Four Paths to an Industrialized World - McNabb, David E. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
A Comparative History of Commerce and Industry, Volume I offers a subjective review of how the cultural, social and economic institutions of commerce and industry evolved in industrialized nations to produce the institution we now know as business enterprise.